If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + -4(y + -2) = 5y Reorder the terms: 19 + -4(-2 + y) = 5y 19 + (-2 * -4 + y * -4) = 5y 19 + (8 + -4y) = 5y Combine like terms: 19 + 8 = 27 27 + -4y = 5y Solving 27 + -4y = 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 27 + -4y + -5y = 5y + -5y Combine like terms: -4y + -5y = -9y 27 + -9y = 5y + -5y Combine like terms: 5y + -5y = 0 27 + -9y = 0 Add '-27' to each side of the equation. 27 + -27 + -9y = 0 + -27 Combine like terms: 27 + -27 = 0 0 + -9y = 0 + -27 -9y = 0 + -27 Combine like terms: 0 + -27 = -27 -9y = -27 Divide each side by '-9'. y = 3 Simplifying y = 3
| x^2+3x+xy=3y | | (X+2)(x-7)=o | | 3y^2+24y+12=0 | | 2x+x=76 | | 33+15=17w-w+4w | | 23=3(M-1)-1 | | 7m-21=42 | | (6+s)-8=2s-23 | | k*k-8=-7 | | 6x+8x-x=-5x | | -1.6(b-3.35)=-11.28 | | 3(x^2)-2+2Sinx=0 | | 2(m+4)=3(m-1) | | 4x^3+3x^2=7x | | 25(2x+1)3+10(2x+1)2-35(2x+1)= | | 2e^3x=-3 | | 12867=x+.467 | | -6=-4+2s | | P=29+2w | | b+b=-6 | | 4r^3+10r^2-6r=0 | | 9+v=v+6 | | 5y-8-3y+2=10 | | 3(1+8x)=-117 | | 4.20*12= | | -11x+1y=-13 | | 6x-4*6=-24 | | 6+2x-2x^2=0 | | 48+3a=7a | | 7t-7=-14 | | 3x+y^4=-y^8 | | 2x+3*x=65 |